Natural resources in Malaysia and Singapore : proceedings - Symposium on Scientific and Technological Research in Malaysia and Singapore (2nd : 1967 : University of Malaya); Stone, Benjamin C. (Benjamin Clemens), 1933- (Kuala Lumpur : University of Malaya, 1969)
36